Search
Ask a question
1

x^2+7x+12/(x=6)(x+3)

Trying to simplify

Comments

1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Steve S. | Tutoring in Precalculus, Trig, and Differential CalculusTutoring in Precalculus, Trig, and Diffe...
5.0 5.0 (3 lesson ratings) (3)
2
(x^2+7x+12)/((x+6)(x+3))
 
= (x+3)(x+4)/((x+6)(x+3))
 
Now we want to "cancel" the x+3 factor in both the numerator and denominator. However, note that:
 
(x+3)/(x+3) = {1 if x ≠ –3, UNDEFINED if x = –3}
 
So we need to constrain our simplified answer:
 
(x+4)/(x+6), x ≠ –3